Gender and Identity Subversion in Oli London's Plastic is Fantastic - Yasmine Anabel Panjaitan; Asyifa Yuditya (Lakon : Jurnal Kajian Sastra dan Budaya, 2022)
The release of Oli London's Plastic Is Fantastic (2021), which talks about his fantasy of plastic surgery, has been extensively criticized. One of the reasons is that his music video was released during Pride Month, a month when the LGBTQ community advocates for their rights for gender equality, followed by other videos and tweets declaring his post-surgery transition to "non-binary" and “Korean.” To dig deeper into this assertion, this study combines Fairclough's (2003) three-dimensional theory as the framework and Machin's (2010) semiotic analysis to examine the song lyrics, visuals, and sociocultural background, thereby contributing to the Multimodal Discourse Analysis studies. This study intends to investigate the construction of gender and identity in Plastic Is Fantastic, the underlying power systems present, and how the power systems subvert gender and Korean identity. Research shows that the lyrics and visuals are connected with Korean identity due to the usage of Korean in the songs and the performer's androgynous appearance and behavior throughout the video. These practices produced problems, especially when his plastic surgery-related social media activity was stirred up by mass media as he consistently equated and exploited his trans status with other minority groups, such as Koreans, LGBTQ, and transracial people. Thus, the subversion of gender and identity is present since identity production is commodified.